Analisis Larangan-Larangan Kegiatan pada Bulan Muharram Menurut Kebudayaan Suku Jawa di Desa Sengon Sari Kecamatan Aek Kuasan Kabupaten Asahan Perspektif Hadis - Hermawan, Bagus; Darta, Ali (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Muharram is known as one of the holy months that has the virtue of worship and certain prohibitions, however in Javanese culture in Sengon Sari Village, Aek Kuasan District, this month is also considered sacred with a number of taboos passed down from generation to generation. This phenomenon gives rise to a dialectic between cultural norms and religious teachings, especially when some of these prohibitions are not explicitly stated in Islamic sources, thus requiring analysis from the perspective of hadith. This study aims to examine the forms of prohibitions on activities in the month of Muharram according to Javanese culture in Sengon Sari Village and assess their relevance and suitability with Islamic teachings through a study of hadith. The method used is a mixed-method with a descriptive-analytical approach through interviews with traditional leaders, observation of cultural practices, and a review of hadith literature. The results show that Javanese people in the village avoid several activities such as marriage, long travel, moving house, and holding large celebrations in the month of Muharram because they are believed to bring bad luck or disaster. However, from the perspective of the hadith, there is no ṣaḥīḥ basis to support this assumption. In fact, the hadith emphasizes Muharram as a month of worship, particularly with the recommendation of the Ashura fast. This cultural prohibition is more of a myth and an attempt to maintain social harmony than a religious obligation. The implication of this research is the need for education that integrates local wisdom values with a proportional understanding of the hadith, so that traditions can continue to be appreciated as part of cultural identity without obscuring authentic Islamic teachings, while also opening up space for dialogue between religious and traditional leaders in building socio-religious harmony.